Excess mortality versus COVID-19 death rates: a spatial analysis of socioeconomic disparities and political allegiance across US states - Aron, J; Muellbauer, J (University of Oxford, 2021)
Excess mortality is a more robust measure than the counts of COVID-19 deaths typically used in epidemiological and spatial studies. Measurement issues around excess mortality, considering data quality and comparability both internationally and within the US, are surveyed. This paper is the first state-level spatial analysis of cumulative excess mortality for the US in the first full year of the pandemic. There is strong evidence that states with higher Democrat vote shares experienced lower excess mortality (consistent with county-level studies of COVID-19 deaths and partisanship). Important demographic and socio-economic controls from a broad set tested were racial composition, age structure, population density, poverty, income, temperature, timing of arrival of the pandemic and political allegiance. Interaction effects suggest the Democrat vote share effect of reducing mortality was even greater in states where the pandemic arrived early. Omitting political allegiance leads to a significant underestimation of the mortality disparities for minority populations.